KARAKTERISASI DAN SKRINING FITOKIMIA BUAH LABU KUNING (Cucurbita moschata Duch.) - Budiman, Hariyadi; Supriningrum, Risa; Sundu, Reksi (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2024)
Pumpkin (Cucurbita moschata Duch.) is one of the plants that contain carotenoids, water-soluble vitamins, phenolics, flavonoids polysaccharides, mineral salts. Pumpkin is a vegetable that has many health benefits. Empirically, the pulp is used to treat diabetes, hypertension, tumors, immunomodulators and antibacterials. The benefits of a natural material with medicinal properties need to be proven scientifically through research. As a first step, characterization of simplisia and ethanol extract of pumpkin fruit and secondary metabolite content were carried out. This study aims to determine the characteristics of simplisia and pumpkin fruit flesh extract and its secondary metabolite content. Characterization includes specific and non-specific parameters. Pumpkin fruit was extracted by maceration with 70% ethanol and obtained an extract yield of 29.68%. Specific characterization results include organoleptic observations in the form of thick blackish brown extract, bitter taste, and distinctive smell. Organoleptic simplicia simplicial piece, odorless, yellow, and bitter taste. The average level of soluble compounds in water extract is 47.33% and simplisia is 22%, while the average soluble compound in ethanol extract is 51.77% and simplisia is 31.33%. Non-specific characterization results include the average total ash content of extracts of 6.52% and simplisia of 8.33%, acid insoluble ash content test averaged 0.31% extracts and 0.22% simplisia. The average water content was 17.55%. The average specific gravity of the extract was 1.02 g/mL and the results of the total microbial contamination in the extract were 4.2 × 103 colonies/g and simplisia were 4.6 x 103 and the yeast mold number in the extract was 1.3 × 102 colonies/g and simplisia was 1.7 × 102 colonies/g. Pumpkin fruit extract and simplisia contain secondary metabolites including alkaloids, flavonoids, saponins, and terpenoids.